The determinants of Polish movies’ box office performance in Poland - Natalia Gmerek (Journal of Marketing and Consumer Behaviour in Emerging Markets)
This paper provides an empirical analysis of financial performance of movies produced in Poland between 2000 and 2011. To understand the reason for a motion picture’s success in the theatrical channel various factors concerning total domestic box office performance were regressed from the box office results of 207 movies. This study proposes that the success of a movie can be determined by three elements: product attributes, distribution-related variables and information sources. The results show that the production budget, movie type – sequel or adaptation, star power, genre, scope of the movie’s release and audience rating are closely related to box office, influencing it in a positive way. On the other hand, critics’ rating, release date (April, July, August) and strong competitive pressure from other movies have a substantial negative influence on box office. The results suggest that the overall movie quality (product-related variables) has an economically and statistically significant effect on total demand for Polish movies.